2017
DOI: 10.1016/j.smrv.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Coffee, caffeine, and sleep: A systematic review of epidemiological studies and randomized controlled trials

Abstract: Caffeine is the most widely consumed psychoactive substance in the world. It is readily available in coffee and other foods and beverages, and is used to mitigate sleepiness, enhance performance, and treat apnea in premature infants. This review systematically explores evidence from epidemiological studies and randomized controlled trials as to whether coffee and caffeine have deleterious effects on sleep. Caffeine typically prolonged sleep latency, reduced total sleep time and sleep efficiency, and worsened p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
235
4
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(287 citation statements)
references
References 94 publications
13
235
4
13
Order By: Relevance
“…7 The analyses, based on cross sectional field studies, showed that disturbed sleep and short sleep duration were related to increased concentrations of some inflammatory markers, such as C reactive protein (CRP) and interleukin 6, but not others, such as tumour necrosis widely used psychoactive drug in the world and is commonly used to mitigate sleepiness and improve performance. 76 Although it is often assumed that shift workers consume large amounts of coffee to remain alert, data on their coffee intake and whether they engage in particular strategies to improve alertness are lacking.…”
Section: Behavioural Mechanismsmentioning
confidence: 99%
“…7 The analyses, based on cross sectional field studies, showed that disturbed sleep and short sleep duration were related to increased concentrations of some inflammatory markers, such as C reactive protein (CRP) and interleukin 6, but not others, such as tumour necrosis widely used psychoactive drug in the world and is commonly used to mitigate sleepiness and improve performance. 76 Although it is often assumed that shift workers consume large amounts of coffee to remain alert, data on their coffee intake and whether they engage in particular strategies to improve alertness are lacking.…”
Section: Behavioural Mechanismsmentioning
confidence: 99%
“…All participants were instructed to refrain from caffeine or alcohol and to maintain their regular cycle of sleeping-waking for 2 days before the experiment, in order to avoid the detrimental effects of caffeine on slow activity, sleep instability, and sleep macrostructure. 15 The 2 groups were age and sex matched (Epileptic group 5 males, age 44.267 ± 4.838 years; range 19-76 years; Controls 5 males, 48.070 ± 5.353 years; range 19-77 years). Sleep macrostructure features of both groups are reported in Table 2.…”
Section: Subjects Patients and Experimental Designmentioning
confidence: 99%
“…Ten to 20 minutes of EEG data free from artifacts were selected at multiple time points during the wake time. Power spectral density (PSD) analysis was performed employing the EEGLab toolbox for Matlab, 17 with 1-Hz frequency resolution and computed on 30-second epochs for delta (1)(2)(3)(4), theta (5-7 Hz), alpha (8)(9)(10)(11), sigma (12)(13)(14)(15), and beta (16-20 Hz) bands. Data cleaning was based on visual inspection and performed after sleep staging in order to preserve the estimation of sleep macrostructure.…”
Section: Eeg Recording and Analysismentioning
confidence: 99%
“…However, recent studies relating coffee/caffeine consumption to health problems. However, in up to date years, most research has suggested that coffee actually has health benefits [4][5][6]. The caffeine in coffee is a bioactive compound with stimulatory property on the central nervous system and a positive outcome on long-term memory.…”
Section: Introductionmentioning
confidence: 99%